Synergistic antifungal effectiveness of essential oils from andean plants combined with commercial drugs - Beatriz Lima; Maximiliano Sortino; Alejandro Tapia; Gabriela E Feresin (International Journal of Pharmaceutical Sciences and Developmental Research - Peertechz Publications, 2022)
The appearance of antifungal resistance promotes the investigation of therapeutic options. There are few studies on the combined effect of antifungal drugs and essential oils (EOs). In the present work, regarding the association of eight EOs Andean plants with antifungal agents against a panel of fungi strains. Combinatorial effects were determined using the Fractional Inhibitory Concentration Index (FICI) and Dose Reduction Index (DRI). A combination of A. cryptantha-B EO with fluconazole showed a synergistic effect against C. Albicans (FIC = 0.31 and DRI = 16.25). EOs from A. cryptantha-A and L. integrifolia showed an additive effect (FICI = 0.75) against C. neoformans. A combination of EOs from A. seriphioides and A. cryptantha-A with terbinafine showed an additive effect on T. rubrum (FIC = 0.56; DRI = 16) and M. gypseum (FICI = 1.03; DRI = 32). In conclusion, combinations between EOs of species from Andean plants and commercial antifungal drugs yielded some interesting findings, as potential antifungal strategies used for treating infections associated with C. Albicans and T. rubrum.